∫ − ∞ ∞ e − ( x 2 y + x y 2 + x y ) ( x 2 y + x y 2 + x y ) d x = 0
For constant y with ℜ ( y ) > 0 , the equation above holds true. Find y 3 + 2 y 2 + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did almost the same as Amal Hari's solution below. First complete the square in both the exponent and the factor: x 2 y + x y 2 + x y = y ( x 2 + x ( y + 1 ) ± 4 ( y + 1 ) 2 ) = y ( x + 2 y + 1 ) 2 − 4 y ( y + 1 ) 2 = : y u 2 − c Notice 4 c is the value we need to find. Insert the simplifications and use u -substitution with the shift above: 0 = ∫ R e − y u 2 + c ( y u 2 − c ) d u = e c ∫ R e − y u 2 ( y u 2 − c ) d u ∣ : e c = 0 ( ∗ ) Use integration by parts to simplify the first integrand and get two "Gaussian Integrals": ∫ R u 2 e − y u 2 d u = − u ⋅ 2 y e − y u 2 ∣ ∣ ∣ ∣ ∣ − ∞ ∞ + 2 y 1 ∫ R 1 ⋅ e − y u 2 d u = 0 + 2 y 1 ⋅ y π Insert the solutions of both "Gaussian Integrals" into our equation ( ∗ ) : 0 = y π ( 2 y y − c ) ⇒ y 3 + 2 y 2 + y = 4 c = 2
Problem Loading...
Note Loading...
Set Loading...
x 2 y + x y 2 + x y = x 2 y + x ( y 2 + y ) = ( x y + 2 y y 2 + y ) 2 − ( 2 y y 2 + y ) 2
for simplicity let ( 2 y y 2 + y ) 2 = m 2 , a constant
we have x 2 y + x y 2 + x y = ( x y + m ) 2 − m 2
∫ − ∞ ∞ ( ( x 2 y + x y 2 + x y ) e − ( x 2 y + x y 2 + x y ) d x = ( ( x y + m ) 2 − m 2 ) e − ( ( x y + m ) 2 − m 2 ) d x )
∫ − ∞ ∞ ( ( x y + m ) 2 − m 2 ) e − ( ( x y + m ) 2 − m 2 ) d x = ∫ − ∞ ∞ ( x y + m ) 2 e m 2 e − ( x y + m ) 2 d x − ∫ − ∞ ∞ m 2 e m 2 e − ( x y + m ) 2 d x
by transforming x y + m = u , we have
∫ − ∞ ∞ y u 2 e m 2 e − u 2 d u − ∫ − ∞ ∞ y m 2 e m 2 e − u 2 d u
we can solve each one separately:
∫ − ∞ ∞ y m 2 e m 2 e − u 2 d u = ∫ − ∞ ∞ y m 2 e m 2 e − u 2 d u
This is a Guassian integral scaled by a factor of y m 2 e m 2
∫ − ∞ ∞ y e m 2 e − u 2 d u = y m 2 e m 2 × π
Similarly,
∫ − ∞ ∞ y u 2 e m 2 e − u 2 d u = y e m 2 ∫ − ∞ ∞ u 2 e − u 2 d u
this is 2 1 the Gaussian integral ( you can verify it by using integration by parts), scaled by a factor of y e m 2
Therefore ∫ − ∞ ∞ y u 2 e m 2 e − u 2 d u = 2 y π e m 2
Now we have ∫ − ∞ ∞ y u 2 e m 2 e − u 2 d u − ∫ − ∞ ∞ y m 2 e m 2 e − u 2 d u = 2 y π e m 2 − y π m 2 e m 2 = 0
By rearranging we will get m 2 = 2 1
From our initial simplification ( 2 y y 2 + y ) 2 = m 2
( 2 y y 2 + y ) 2 = 1 / 2
rearrange again to get y 2 + y = 2 y
Square the expression:
y 4 + 2 y 3 + y 2 = 2 y
factor the y
y 3 + 2 y 2 + y = 2